2007
DOI: 10.1162/jocn.2007.19.5.855
|View full text |Cite
|
Sign up to set email alerts
|

Comprehending Prehending: Neural Correlates of Processing Verbs with Motor Stems

Abstract: The interaction between language and action systems has become an increasingly interesting topic of discussion in cognitive neuroscience. Several recent studies have shown that processing of action verbs elicits activation in the cerebral motor system in a somatotopic manner. The current study extends these findings to show that the brain responses for processing of verbs with specific motor meanings differ not only from that of other motor verbs, but, crucially, that the comprehension of verbs with motor mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
128
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 38 publications
(50 reference statements)
22
128
1
1
Order By: Relevance
“…Planned pair-wise comparisons indicated that simple cognate motor verbs elicited more activation in the S2 ROI than simple cognate nonmotor verbs (t¼ 2.94, p o.01), whereas complex motor and nonmotor verbs did not differ (t¼ À.20, p¼ .84). These results suggest that motor-related activations are only seen with simple verbs and not with opaque complex verbs, replicating Rüschemeyer et al's (2007) findings.…”
Section: Roi Analysessupporting
confidence: 81%
See 4 more Smart Citations
“…Planned pair-wise comparisons indicated that simple cognate motor verbs elicited more activation in the S2 ROI than simple cognate nonmotor verbs (t¼ 2.94, p o.01), whereas complex motor and nonmotor verbs did not differ (t¼ À.20, p¼ .84). These results suggest that motor-related activations are only seen with simple verbs and not with opaque complex verbs, replicating Rüschemeyer et al's (2007) findings.…”
Section: Roi Analysessupporting
confidence: 81%
“…However, they can also be used as a tool to investigate whether morphologically complex words are decomposed into their constituent parts or processed holistically during comprehension. As far as we know, this approach has so far only been used in Rüschemeyer et al's (2007) study on German as L1. In this study, morphologically complex derivations (i.e.…”
Section: Embodiment Effects With Morphologically Complex Words: Decommentioning
confidence: 99%
See 3 more Smart Citations